Efficacious fluorescence turn-on probe for high-contrast imaging of human cells overexpressing quinone reductase activity. Issue 4 (21st December 2016) - Best, Quinn A.; Prasai, Bijeta; Rouillere, Alexandra; Johnson, Amanda E.; McCarley, Robin L.
Abstract : A turn-on substrate probe is activated by an oxidoreductase, offering fluorescence images of cancer cells with unprecedented positive signal-to-negative background ratios. Abstract : We report a new turn-on substrate probe whose intense fluorescent reporter signature is selectively provided upon probe activation by the cancer-associated oxidoreductase, hNQO1. The extremely high fluorescence turn-on of the probe was utilized to generate fluorescence microscope images of hNQO1-expressing, tumor-derived colorectal and ovarian cancer cells with unprecedented positive signal-to-negative background ratios (PNRs), a key step toward probe application in guided surgical removal of diseased tissues.